2012
DOI: 10.1371/journal.pone.0031871
|View full text |Cite
|
Sign up to set email alerts
|

Two Cellular Protein Kinases, DNA-PK and PKA, Phosphorylate the Adenoviral L4-33K Protein and Have Opposite Effects on L1 Alternative RNA Splicing

Abstract: Accumulation of the complex set of alternatively processed mRNA from the adenovirus major late transcription unit (MLTU) is subjected to a temporal regulation involving both changes in poly (A) site choice and alternative 3′ splice site usage. We have previously shown that the adenovirus L4-33K protein functions as an alternative splicing factor involved in activating the shift from L1-52,55K to L1-IIIa mRNA. Here we show that L4-33K specifically associates with the catalytic subunit of the DNA-dependent prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 70 publications
6
16
0
Order By: Relevance
“…The Ad E4orf3 and E4orf6 proteins were reported to bind DNA-PK and to inhibit viral DNA concatenation and V(D)J recombination, which relies on NHEJ, a repair process regulated by DNA-PK (30). It was also shown that the Ad L4-33K protein associates with the catalytic subunit of DNA-PK (31). L4-33K functions as an alternative splicing factor involved in activating the shift from the earlier-appearing L1-52,55K mRNA to the later L1-IIIa transcript.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ad E4orf3 and E4orf6 proteins were reported to bind DNA-PK and to inhibit viral DNA concatenation and V(D)J recombination, which relies on NHEJ, a repair process regulated by DNA-PK (30). It was also shown that the Ad L4-33K protein associates with the catalytic subunit of DNA-PK (31). L4-33K functions as an alternative splicing factor involved in activating the shift from the earlier-appearing L1-52,55K mRNA to the later L1-IIIa transcript.…”
Section: Discussionmentioning
confidence: 99%
“…Because we found that during Ad infection, DNA-PK was eventually inhibited by E4orf4 (Fig. 3), and as it was reported that DNA-PK was the target of additional Ad proteins besides E4orf4 (30,31), we investigated the effect of DNA-PK inhibition on the efficiency of Ad replication using three different cell lines. First, HeLa cells were infected with dl366* or dl366*ϩE4orf4 virus, in the presence or absence of a DNA-PK inhibitor added at a concentration that efficiently inhibited this enzyme (Fig.…”
Section: Figmentioning
confidence: 99%
“…The Ad L4-33K protein is a virus-encoded alternative RNA splicing factor which activates splicing of Ad late gene transcripts that contain weak 3= splice sites (8). The L4-33K protein may be phosphorylated by two cellular protein kinases: DNA-dependent protein kinase (DNA-PK) and protein kinase A (PKA) (9). L4-33K interacts with the catalytic subunit of DNA-PK, and phosphorylation by DNA-PK has an inhibitory role in L4-33K-mediated alternative RNA splicing.…”
mentioning
confidence: 99%
“…L4-33K interacts with the catalytic subunit of DNA-PK, and phosphorylation by DNA-PK has an inhibitory role in L4-33K-mediated alternative RNA splicing. On the other hand, the phosphorylation of L4-33K by PKA stimulates L4-33K-mediated alternative RNA splicing (9). Through this process, L4-33K is believed to coordinately control late gene expression to optimize the conditions for maximal virus production.…”
mentioning
confidence: 99%
“…Another important aspect of genome regulation is alternative splicing. G. Akusjarvi (University of Uppsala, Sweden) showed data to indicate that the late viral splice site regulatory protein L4-33K, which controls alternative splicing of the viral L1 transcript, is phosphorylated by DNA-dependent protein kinase (DNA-PK) and protein kinase A (PKA) (Tormanen Persson et al, 2012). Phosphorylation by DNA-PK inhibits while phosphorylation by PKA enhances L1-IIIa alternative splicing.…”
Section: Transcriptional Regulation and Replicationmentioning
confidence: 99%